A viabilidade e efetividade de um Programa de Reabilitação Vestibular Personalizado na Atenção Primária à Saúde - Maria Clara Corrêa Peixoto (2015)
AIM: To evaluate the viability and effectiveness of the Personalized Vestibular Rehabilitation Program on the Primary Health Care. METHOD: Trough an experimental and broad prospective research, with users of the Unified Health System (hereby SUS) in the areas embraced by the Guaranis Health Centers (Centro de Saúde Guarani) and Jardim Felicidade II of Sectional North in the city of Belo Horizonte. The users with complaints of dizziness were referred by the doctor of the Family Health Team to speech therapy evaluation. Those users with indications to Vestibular Rehabilitation were included on the Personalized Vestibular Rehabilitation Program; which involves orientation, vestibular habituation exercises, therapeutic maneuvers, supervision, and final evaluation. The participants were attended individually on weekly meetings. All must do the quiz Brazilian Dizziness Handicap Inventory (DHI-Brasileiro) before and after their participation in the Program. At the end, the users are referenced to the Family Health Team, through matricial meetings, which are monthly. A database was built specifically for this research and it was used the SPSS 19.0 software. For descriptive analysis purposes, it is performed in the frequency distribution of the categorical variable involved in the evaluation in studies and analyses of the measures of central tendency and dispersion of continuing variables. It showed the viability of this Program on Primary Health Attention and its effectiveness through the increasing of the quality of life of the users, with reduction of the complaints and increasing in quality of life; contributing so to the solvability and integrality increasing on the Primary Health Attention care.